Cloud infrastructure solution: Building cost effective model for real time hands-on labs using computing methodologies for productive learning solutions in academics - Madhukar Ghorpade, Yogesh; Dr. R. Kamatchi, Prof. (International Journal of Engineering and Technology, 2018)
By in 2021, more than half of global enterprises already using cloud today adopt an all in cloud strategy [6]. Is today the world of modern infrastructure using digital transformation results cost effective approach? If yes, than how it has to be transformed and if No, than what are the differences between approaches applied. The cost effective methodology and its implementation is primary approach towards cost computing to bring effectiveness with the proper requirements and provides proper solution.The productive learning with different approach is the vital requirement for todayâ€™s Cloud infrastructure building from studentâ€™s perspective needs to be understood [13 - 15]. The paper aims in building and implementing the Lab infrastructure using developed model for cost effective approach by comparing On-premise vendors with cloud vendors. The technology that is used for the experiment are open-source and Proprietary. The paper results with the best approach used in cost computing methodology providing best solution for the given requirement in academic environment.Â